Systematic design of ADRC-based unmanned tracked vehicle trajectory tracking with FPGA-in-the-loop validation - Stanković, Momir; Madonski, Rafal; Manojlović, Stojadin (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The trajectory tracking control problem in an unmanned tracked vehicle (UTV) represents a challenging task, due to unknown and unmeasurable slippage dynamics which inevitably exists during movement. Therefore, the application of standard industrial control schemes is often limited. Methods: In this paper, an active disturbance rejection control (ADRC) scheme is proposed for the longitudinal (vehicle longitudinal velocity control) and lateral (vehicle course angle control) control channels of the UTV to collectively handle all the plant modeling uncertainties and acting slippage disturbances. Results: A step-by-step procedure for applying the ADRC algorithm for the specific case of UTV trajectory tracking is presented. It includes systematic design, discretization as well as performance analysis and validation utilizing FPGA-in-the-loop (FIL) simulations. Conclusions: The proposed FIL-based validation method reduces the gap between pure simulation design (which may be too idealized) and implementation on the real vehicle (which may be time-consuming). The obtained experimental results show the advantages of the proposed control structure over standard industrial PI/PID controllers in different working conditions.